(untitled) (London Journal of Research In Humanities and Social Sciences, 2024)
Art and design as disciplines complement each other within the horizon of culture for sustainability. There are designers and artists who use methods and practices within their specific fields to produce meaning through their devices and artifacts. From the perspective of building a collective culture for environmental protection, some strategies emerge in the planning of a sustainable future. The articulation between art and design is one of the strategies found by the Brazilian designers, the Campana Brothers. This article addresses the cultural production articulated by the design-art (author design) of these designers. Through this investigation, we seek to establish a correlation between art and design with the logic of sustainability and environmental care as a semantic vector. As an underlying issue, we question how art and design, in their approach as author design, can contribute to the culture of sustainability. The method used is qualitative with an exploratory bias. As an expected result, this article aims to qualify the research currently conducted within the creative field between design and art.